Evaluation of bioflavonoids on the immediate and delayed microtensile bond strength of self-etch and total-etch adhesive systems to sound dentin - Rajeswari Kalaiselvam; Arathi Ganesh; Mathan Rajan; Deivanayagam Kandaswamy (Wolters Kluwer Medknow Publications, 2018)
Aim: This study aims to evaluate the effect of two bioflavonoids (epigallocatechin-3-gallate [EGCG] and catechin) and a protein inhibitor (chlorhexidine [CHX]) on the immediate and delayed microtensile bond strength of self-etch and total-etch adhesive systems to sound dentin. Materials and Methods: The occlusal surfaces of 96 mandibular human third molar teeth specimens were ground after removal of the excess tissues, to expose the middle dentin. The dentin specimens were randomly allocated into four groups, each consisting of 24 teeth (n = 24) according to the application of the enzyme inhibitor. The adhesive system used in this study was Adper easy bond, a self-etch adhesive system, and Adper Single Bond 2, a total-etch adhesive system. Microtensile bond strength testing was conducted using thermocycler 2000, Heto-Holten A/S. Results: All the three enzyme inhibitors increase the bond strength values of the resin-dentin interphase when used during dentin bonding. The EGCG enzyme inhibitor has shown the highest immediate bond strength to dentin when used with both the adhesive systems.